Slip Length Measurements Using µPIV and TIRF‐Based Velocimetry. Issue 11 (19th October 2014) - Li, Zhenzhen; D'eramo, Loic; Monti, Fabrice; Vayssade, Anne‐Laure; Chollet, Benjamin; Bresson, Bruno; Tran, Yvette; Cloitre, Michel; Tabeling, Patrick
Abstract The goal of this paper is to review progress (mostly recent) made in micro and nanovelocimetry, focusing on two techniques: µPIV (microparticle image velocimetry) and nanoPTV (nanoparticle tracking velocimetry). The paper focuses on the measurement of slippage (taken as a benchmark for these techniques), concentrating on work done in our group. We review the developments of µPIV that led, in the last ten years, to the achievement of 100 nm accuracy in the measurement of slip lengths. Later, this approach was complemented by nanoPTV, which recently obtained ±5 nm precision. Here, we also mention recent application of these techniques toward better characterization of microgel and polymer flows. As a whole, the two techniques have conveyed valuable information on flow behavior within and close to the boundaries of microchannels, on the importance of wetting, and on the role of surface heterogeneities. µPIV is commercially available but nanoPTV is not mature. Interesting instrumental developments are expected in the future for the latter technique.